Using Quality Function Deployment (Qfd) in Designing the “Green Practice” of Gscm For Malaysia’s SMEs Industries - Norlinda, Mohd Rozar; Abdullah, Ibrahim; Muhammad Ashlyzan, Razik (IJAIEM, 2015)
The worldwide is now much debated about the environmental problem and the preservation. In the meantime, GSCM has been introduced and accepted by many environmental experts and to apply this concept to solve the environmental problems. Unfortunately, found that many studies just discussed about the constraints and drivers of GSCM in the industries and not to the problem solving for environment awareness. Therefore, this study will focus on the design of green practice for the environmental awareness with considering the constraints of the customer requirements in the industries. The factor analysis and correlations analysis were used to complete the design in satisfying the requirements of the customer constrained by the limited resources of the technical requirements. Among the methods to fulfill the area of this study is the quality function deployment (QFD) and it was used to identify the desirable the design in green practice of GSCM in Malaysia’s SMEs industries.